2017
DOI: 10.21103/article7(3)_shc2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Special Endurance of Athletes in Freestyle Wrestling at the Preparatory Stage of a Sports Cycle

Abstract: We evaluated the special endurance (SE) of freestyle wrestlers with the help of complex tests of special working capacity, while simultaneously monitoring the change in levels of lactate concentration and LPO in the blood at the preparatory stage of the annual sport cycle. A total of 23 athletes with high sports qualification participated in the experiment. Athletes were tested in the field by "repeated marginal load" tests, including the operational test (OT) developed by the authors. The most noticeable shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Studies have shown that the muscular balance in the lower extremities is related to the general body balance and oxygen utilization capacity, and that a developed muscular balance positively affects these parameters (Heitkamp et al, 2001;Silva et al, 2018). These variables are of vital importance for wrestling and it is known that an athlete with advanced motor features is advantageous during the wrestling match (Kuzmina et al, 2017;Moran-Navarro et al, 2015;Murlasits, 2004). Without any special strength training, pure wrestling training does not provide a significant improvement on the flexor muscles of the athletes (Tatlici et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the muscular balance in the lower extremities is related to the general body balance and oxygen utilization capacity, and that a developed muscular balance positively affects these parameters (Heitkamp et al, 2001;Silva et al, 2018). These variables are of vital importance for wrestling and it is known that an athlete with advanced motor features is advantageous during the wrestling match (Kuzmina et al, 2017;Moran-Navarro et al, 2015;Murlasits, 2004). Without any special strength training, pure wrestling training does not provide a significant improvement on the flexor muscles of the athletes (Tatlici et al, 2021).…”
Section: Discussionmentioning
confidence: 99%